2006
DOI: 10.4049/jimmunol.176.12.7768
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Is Increased in Dendritic Cells in Multiple Sclerosis and Down-Regulation of IL-23 by Antisense Oligos Increases Dendritic Cell IL-10 Production

Abstract: IL-23 is a heterodimeric cytokine comprising a p19 subunit associated with the IL-12/23p40 subunit. Like IL-12, IL-23 is expressed predominantly by activated dendritic cells (DCs) and phagocytic cells, and both cytokines induce IFN-γ secretion by T cells. The induction of experimental autoimmune encephalitis, the animal model of multiple sclerosis (MS), occurs in mice lacking IL-12, but not in mice with targeted disruption of IL-23 or both IL-12 and IL-23. Thus, IL-23 expression in DCs may play an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
4

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(128 citation statements)
references
References 34 publications
4
119
0
4
Order By: Relevance
“…Interestingly, evidence is accumulating in recent years that psoriasis may be a multisystem disease involving even coronary arteries and the heart [25,39,40]. Epidermal thickening (acanthosis) of the skin is a hallmark of psoriasis.…”
Section: Psoriasismentioning
confidence: 99%
“…Interestingly, evidence is accumulating in recent years that psoriasis may be a multisystem disease involving even coronary arteries and the heart [25,39,40]. Epidermal thickening (acanthosis) of the skin is a hallmark of psoriasis.…”
Section: Psoriasismentioning
confidence: 99%
“…In contrast, it is well known that dysregulated production of IL-17 is associated with human autoimmune diseases, including multiple sclerosis, inflammatory bowel disease, and psoriasis [6,7,8,9]. Importantly, studies in a murine experimental arthritis model showed IL-17 to be involved in both the initiation and the progression of disease.…”
Section: Introductionmentioning
confidence: 98%
“…IL17, IL17F and its regulator IL23 appear to be important in host defense against extracellular bacteria and fungi (28)(29)(30). Additionally, a number of autoimmune diseases, such as psoriasis and inflammatory bowel disease, are associated with over-production of these cytokines and interference with IL17 production or action attenuates autoimmune disease (31)(32)(33)(34)(35)(36). Polymorphisms in 5.…”
Section: Discussionmentioning
confidence: 99%